Criminal Responsibility Of Defamation Under The Indonesian Criminal Law - Aryansyah, Aryansyah; Parmono, Budi; Muhibbin, Muhibbin (International Journal of Law, Environment, and Natural Resources, 2022)
The Research, "Responsibility of Defamation Actors in Indonesian Positive Law Studies" aims to describe the arrangements for criminal acts of defamation in the Indonesian criminal law system as well as analyze criminal responsibility for perpetrators of defamation in the Indonesian criminal law system. This research is a normative legal research, which examines laws and regulations in a coherent legal system as well as unwritten legal values ??that live in society, which are related to the responsibility of perpetrators of defamation in the perspective of positive law in Indonesia. The results of the research can be presented in an outline: Arrangements for criminal acts of defamation in Indonesian criminal law are regulated in the Criminal Code (KUHP), and the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to the Law of the Republic of Indonesia No. 11 of 2008 concerning Information and Electronic Transactions. The Criminal Code regulates Article 310 paragraph (1) and paragraph (2), as well as Article 311 paragraph (1) of the Criminal Code. Whereas in the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to the Law of the Republic of Indonesia No. 11 of 2008 concerning Information and Electronic Transactions regulated in Article 27 paragraph (3); Criminal responsibility for defamation in the Indonesian criminal law system is borne by anyone who intentionally attacks the reputation or reputation of a person, by accusing something with clear intentions so that it is publicly known (Article 310 paragraph (1) of the Criminal Code), and is also borne by every a person who intentionally and without rights distributes and/or transmits and/or makes accessible Electronic Information and/or Electronic Documents that contain insults and/or defamation (Article 27 paragraph (3) of Law Number 19 of 2016 concerning Amendments to Law of the Republic of Indonesia No. 11 of 2008 concerning Information and Electronic Transactions